Analisa numerik pengaruh diameter perforate terhadap perpindahan panas dan penurunan tekanan pada saluran segi empat 4:1 menggunakan perforated groove v- rib - Khairul Umurani; Arya Rudi Nasution (Badan Kerja Sama Teknik Mesin Indonesia, 2022)
In the internal cooling ducts of the gas turbine blades, the rib structure is widely used to enhance convective heat transfer with the flow of coolant passing through the rib surface. This research concentrates on the perforated V-rib with grooved in the cooling channel with a rectangular cross-section. This research analyzes the heat transfer and pressure drop in the rectangular channel with a perforated groove v-rib to provide the cooling blade gas turbine solution. This research was conducted by numerical analysis. Several models were created and analyzed using Solidworks Flow Simulation, a commercial computational fluid dynamics (CFD) based on the finite volume method. Solidworks Flow Simulation Solver to analyze laminar and turbulent flow using the Reynolds averaged Navier-Stokes equation. Using the same transport equations for laminar and turbulent flows provides flexibility. Turbulence in the flow is treated using turbulent kinetic energy (k) and turbulence dissipation rate (ꞷ) using the standard k-ꞷ turbulence model. The Reynolds numbers 2000, 4000, 6000, 8000, 10000,12000,14000. By giving 1000 Watts of heat at the bottom of the channel, the air condition at the inlet temperature is 30 oC and a pressure of 1 atm. In the flow regime of 2000 < Re < 20,000, perforated rib construction significantly increases the Nusselt number compared to no rib. The coefficient of friction for the solid rib configuration is higher than for the rib with holes.